Acute Toxicity Study and Anti-Nociceptive Activity of Ethanol Extract of Aesculus Indica Seeds on Experimental Animal Models - More, Priyanka R; Velhal, Atish B; Chaware, Vitthal J; K. Redasani, Vivek Kumar (Asian Journal of Pharmaceutical Research and Development, 2021)
Aesculus indica, widely known as the horse chestnut tree, has long been used as antiangiogenic, antibacterial, antidiabetic, antiviral and antifungal. Ttraditionally it has been used as medicine for the treatment of skin diseases, rheumatism and different pain conditions. The current study was undertaken to investigate possible effects of ethanol extract of seeds of plant in experimentally produced pain in animals because there were no scientific publications on the use of Aesculus indica seeds for anti-nociceptive activity. Preliminary phytochemical screening revealed the presence of flavonoids, tannins, carbohydrates, Saponins, and phenolic substances in the extract. The OECD guideline 423 was followed for acute toxicity testing.At a dose of 2000 mg/kg, the extract was confirmed to be safe. The anti-nociceptive effect of three distinct dose levels of extract (100, 200, and 300 mg/kg) was tested in Swiss albino mice using a hot plate, tail immersion test, and acetic acid induced writhing. Extract had strong anti-nociceptive efficacy (P < 0.001) in a hot plate test. The extract significantly increased the tail withdrawal reaction in the tail immersion test (P < 0.001).The extract considerably reduced the number of writhes in the acetic acid writhing test (P < 0.001). The findings indicate that the extract has substantial anti-nociceptive effect.